2020
DOI: 10.3389/fpsyt.2020.00308
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Rich Club Organization of Structural Network as a Neuroimaging Feature in Relation With the Severity of Primary Insomnia

Abstract: Purpose: Insomnia is the most prevalent sleep complaint in the general population but is often intractable due to uncertainty regarding the underlying pathomechanisms. Sleep is regulated by a network of neural structures interconnected with the core nodes of the brain connectome referred to as the "rich club". We examined alterations in brain rich-club organization as revealed by diffusion tensor imaging (DTI) and the statistical relationships between abnormalities in rich-club metrics and the clinical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…The rich-club organization described in the human connectome is a high-capacity central core that comprises a set of regions (22) which are suggested to form an information backbone; it is crucial for brain function and vulnerable to pathogenic agents of disease (23). Consequently, rich-club organization has been studied in several brain disorders, including Alzheimer's disease (24,25), schizophrenia (26), insomnia (27), and stroke (28). Antonakakis et al (18) identified with magnetoencephalography (MEG) that patients with mTBI demonstrate hyper-synchronization among rich-club regions compared with healthy controls (HCs) in the δ band and the δ-γ1, θ-γ1, and β-γ2 frequency pairs.…”
Section: Introductionmentioning
confidence: 99%
“…The rich-club organization described in the human connectome is a high-capacity central core that comprises a set of regions (22) which are suggested to form an information backbone; it is crucial for brain function and vulnerable to pathogenic agents of disease (23). Consequently, rich-club organization has been studied in several brain disorders, including Alzheimer's disease (24,25), schizophrenia (26), insomnia (27), and stroke (28). Antonakakis et al (18) identified with magnetoencephalography (MEG) that patients with mTBI demonstrate hyper-synchronization among rich-club regions compared with healthy controls (HCs) in the δ band and the δ-γ1, θ-γ1, and β-γ2 frequency pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the FCS method calculated by degree centrality was used to explore the abnormal brain areas in CI patients without combining this method with brain structural methods based on 3D-T1WI, DTI, etc. However, our team has explored brain structural alterations and the mechanism of CI in the past ( 53 , 76 , 77 ). In the future, we will further explore the complex mechanism of the interaction between brain functional and structural alterations and the GM in CI patients to screen for more accurate imaging biomarkers for MGBA interaction mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It probably revealed that the rich-club connections among central hubs, which worked as high-cost and high-capacity backbone of global brain communication (Power et al 2013; van den Heuvel et al 2012), had higher tendency to be impaired in PD-pRBD patients. Structural networks in primary insomnia DTI studies have suggested that abnormal rich club connections, mainly in the limbic cortices and basal ganglia circuit network, were associated with primary insomnia severity (Wu et al 2020). However, rich club organization in PD-pRBD has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%